THE ROLE OF CONTROLLING IN THE ENTERPRISE DEVELOPMENT MANAGEMENT SYSTEM - KUSHCH, Anastasiia; POCHTOVYUK, Andryi (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article investigates the essence, role, and functions of controlling within the modern enterprise management system. It outlines how controlling has evolved from a purely analytical accounting tool into a key component of strategic management that contributes to increasing efficiency, ensuring adaptability, and enhancing enterprise competitiveness. The theoretical foundations of controlling are examined along with its practical application in managerial processes, particularly in the context of uncertainty and crisis conditions. The study pays special attention to the classification of types of controlling (strategic, operational, functional) and to its integration into the decision-making process at various organizational levels. It is emphasized that controlling serves not only as an internal information and coordination system, but also as a strategic tool that enables enterprises to align resources with goals, monitor performance, and respond promptly to internal and external changes. The analysis reveals that the successful implementation of controlling ensures transparency of business processes, contributes to cost optimization, and supports the development of sustainable growth strategies. The article highlights the experience of companies that effectively apply controlling practices and demonstrates the benefits of data-based decision-making in a dynamic business environment. The research concludes that in the modern economic environment, the implementation of controlling should be seen as a crucial element of enterprise management. It contributes to improving management efficiency, achieving strategic objectives, and maintaining flexibility in response to market demands and competition.